ANALISIS MANAJEMEN SYARIAH TERHADAP PENERAPAN STRATEGI MARKETING MIX DALAM PEMASARAN PRODUK-PRODUK BANK SYARIAH MANDIRI KANTOR CABANG BOGOR - Dewi Amalia; Tubagus Rifqy Thantawi; Azizah Mursyidah (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
In an effort to maintain business stability of Islamic banks is not an easy job because Islamic banks are required to be able to compete with other banking institutions in running their business, especially in the development of products that are traded. In addition, Islamic banks are also required to be able to provide services according to the wishes of customers so that customers remain loyal to buy the services/products offered. The research aims to analyze the marketing mix strategy in marketing products at Bank Syariah Mandiri Bogor Branch and analysis of sharia management on the implementation of the Marketing Mix strategy in marketing products at Bank Syariah Mandiri Bogor Branch. This research is qualitative in nature and its data collection methods use interviews, documentation and observation. Processing and analysis of data using interactive form of qualitative analysis method. The results of the research conducted found that (1) Implementation of the Marketing mix strategy, by combining Product Strategy, Price Strategy, Location Strategy and Lay Out, Promotion Strategy at BSM Bogor Branch in general can run well; (2) Sharia management analysis of the implementation of marketing mix strategies such as product strategy, price strategy, place strategy, and promotion strategy in marketing Bank Syariah Mandiri Bogor Branch products through the functions of planning, organizing , actuating, and controlling found a number of things including BSM Bogor Branch has provided the best service to the community or customers, so that the bank is able to provide excellent service and customer care to the community or customers.